Structural Engineering/Perspective Damage Pattern of Temples of Kathmandu Valley after Gorkha Earthquake 2015 - Suwal, Rajan (Journal of Advanced College of Engineering and Management, 2022)
Nepal is well known for traditional temples. It is found that most of the temples were built in12th century to 17th Century. Most of the temples, built in 17th century, in Kathmandu valley were constructed in pagoda style. Timber along with bricks were used for construction and mud or surkhi mortar was used as a binding material. The Gorkha earthquake, 2015 caused minor to major damages to number of temples. Pictures highlighting damages in the temple were collected during damage reconnaissance and is used for studying its structural systems. Possible causes of damage pattern of temples are discussed and recommendations for future construction are given.